A sequel to Cuore? De Amicis and Mantegazza, the story of a literary feud (Prassi Ecdotiche della Modernità Letteraria, 2025)
Based on unpublished material, this article aims to reconstruct the relationship between the scientist Paolo Mantegazza, author of a sequel to Cuore entitled Testa (1887), and Edmondo De Amicis. Their relationship appeared friendly but was in fact marked by mutual envy. An analysis of the letters sent by the publisher Emilio Treves to Mantegazza also provides useful insights into the publishing history of De Amicis’s masterpiece, its immediate reception, and the planning of a follow-up volume.
Keywords: Paolo Mantegazza; Edmondo De Amicis; Emilio Treves; History of Publishing; archives